Social robots helping people with dementia: Assessing efficacy of social robots in the nursing home environment - Moyle, W.; Jones, C.; Cooke, M.; O'Dwyer, S.; Sung, Billy; Drummond, S. (2013)
This paper explores the challenges of testing the efficacy of social robots in the nursing home environment. The findings of two projects exploring the use of PARO and Giraff (a telepresence robot) are outlined. The challenges experienced by the researchers when undertaking a randomized controlled trial and using a case study design to test the social robots with people with dementia are examined. While randomized controlled trials are advocated, in early testing of the social robots the case study approach has the advantage that researchers can manipulate and adjust the intervention as issues arise. This can assist in the preparation of a protocol for testing in a randomized controlled trial at a later date.